Amelogenesis imperfecta: Literature review. - Hurtado, Paula-Margarita; Tobar-Tosse, Fabián; Osorio, Julio; Orozco, Lorena; Moreno, Freddy (Revista Estomatología, 2015)
Amelogenesis imperfecta (AI) corresponds to a set of hereditary disorders, which affects the enamel development in people. It affects the enamel histological structure, and the clinical appearance of the temporal and permanent teeth. AI is described by several enamel phenotypes, which includes hypoplastic, hypomaturation and hipocalcified. In this paper is presented a literature review about the genetic origin of the AI.